To write this equation in simplest form, we simply need to combine all like terms. The like terms in this particular expression are the terms with an n-variable and the terms with no variable. So we can combine them to simplify our expression.
5n - 6 + n - 1
First step, we can reorder our terms so that like terms are near each other
5n + n - 6 - 1
Now we can combine easily
(5n + n) - (6 - 1)
6n - 5
And that is your simplified expression.
5n - 6 + n - 1 in simplest form is 6n - 5.
Hope that helped! =)
Answer:
15) 20.4
16) 40.4
17) 2.5
18) 32
Step-by-step explanation:
15) Use the calculator: 42.7/11.1*5.3
16) Use the calculator: 121.1/3
17) Use the calculator: 32.5/ (42.9/3.3)
18) 28.8/ (1.8/2)
1 pint = 2 cups
2 pints = 4 cups
3 pints = 6 cups
4 pints = 8 cups
5 pints = 10 cups
6 pints = 12 cups
7 pints = 14 cups
8 pints = 16 cups
9 pints = 18 cups
10 pints = 20 cups
11 pints = 22 cups
12 pints = 24 cups
13 pints = 26 cups
14 pints = 28 cups
15 pints = 30 cups
Answer:
16%
Step-by-step explanation:
add all of them together (total=18) and divide 3 by the total
You will get 0.16 and you turn it into a percentage by moving the decimal two places to the right
<span>I think any of those estimates are correct since we don't have a value for the width and length so acquiring the actual measurement its impossible. All possible answers are correctly written in square units.</span>